Enzymes produced by bacteria within biofilms of dairy origin and their effect on dairy products : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Palmerston North, New Zealand - Teh, Koon Hoong (Massey University, 2013)
Prior to the current study, there was no scientific evidence that enzymes produced by bacteria within biofilms in milk transport tanker could have a detrimental effect on the quality of dairy products. Bacteria attached to the internal surfaces of milk tankers were isolated, identified, and characterized in terms of their ability to produce heat-stable enzymes (protease and lipase) and to form biofilms. Twelve of the bacterial isolates were identified by 16s DNA sequencing as belonging to the genera Bacillus, Staphylococcus, Streptococcus, Pseudomonas, and Serratia. Six of the dairy bacterial isolates were evaluated for their ability to produce proteolysis in milk when growing within either single culture or co-culture biofilms in an in vitro model system that simulated the upper part of a milk tanker during a typical summer’s day of milk collection in New Zealand. Proteolysis per cfu decreased as the temperature of incubation increased (20-37 °C), and proteolysis per cfu was generally higher within biofilms compared with the corresponding planktonic cultures. Lipolysis by bacteria within biofilms in the in vitro model was investigated using single or co-culture biofilms or planktonic cultures of four dairy bacteria and a known lipase-producing bacterium. The hydrolysis of p-nitrophenol palmitate was at least 10 times higher by bacteria within biofilms (0.01 to 8.35 nU/CFU) than in planktonic cultures (0.01 to 0.07 nU/CFU). The effect of proteases on UHT skim milk was determined by exposing sterile skim milk to a multispecies biofilm formed on an in vitro model of a milk tanker. The amount of free peptides which indicated proteolysis in the UHT milk was monitored over five months of storage. Free peptides were higher in UHT milk that had been made from milk exposed to the multispecies biofilm, than in UHT milk that had been made from milk that had not been exposed to the biofilm. Enzymes that are secreted from biofilms into raw milk during transportation can potentially reduce the quality of dairy products. Improvements at this early stage of dairy manufacture may reduce economic loss in the dairy industry.
Content published as: Teh, K.H., Flint, S., Palmer, J., Lindsay, D., Andrewes, P., & Bremer, P. (2011). Thermo-resistant enzyme-producing bacteria isolated from the internal surfaces of raw milk tankers. International Dairy Journal, 21(10), 742-747. doi: 10.1016/j.idairyj.2011.04.013. .(chapter 3b). Teh, K.H., Flint, S., Palmer, J., Andrewes, P., Bremer, P. & Lindsay, D. (2012). Proteolysis produced within biofilms of bacterial isolates from raw milk tankers. International Journal of Food Microbiology, 157, 28-34. doi: 10.1016/j.ijfoodmicro.2012.04.008. (chapter 4a). Teh, K.H., Lindsay, D., Palmer, J., Andrewes, P., Bremer, P., & Flint, S. (2013). Lipolysis within single culture and co-culture biofilms of dairy origin. International Journal of Food Microbiology, 163(2-3), 129-135. doi: 10.1016/j.ijfoodmicro.2013.02.009. (chapter 4b)
Keywords: Milk microbiology; Biofilm; Enzymes